Morphogenesis of Olfactory Organ of Bushymouth Catfish Ancistrus dolichopterus (Teleostei: Loricariidae) before Switching to Exogenous Feeding - Tytiuk, Olha; Sapoznikov, Olga; Tichý, František; Kloučková, Michaela; Stepanyuk, Yaroslav (Zoological science, 2020)
Olfaction plays an important role in a fish's life. Its value may differ at different developmental stages, depending on the feeding style of the species. The goal of the present study was to investigate the olfactory organ of a species that feeds mainly on algae- the bushymouth catfish, Ancistrus dolichopterus-at developmental stages from olfactory placode to the definitive olfactory chamber. For this study, we used light and electron (scanning) microscopy. The topography of the olfactory placode of A. dolichopterus is typical for teleostei. Formation of olfactory pit takes place at the same time as rostral elevation formation. Rostral elevation participates in the formation of the nasal bridge and anterior tubular nostril. It was found out that the anlage of olfactory rosette in A. dolichopterus arises earlier than in most teleostei. However, the number of lamellae does not increase until switching to exogenous feeding. We suppose that the early development of olfactory organ is necessary for intraspecific communication, not just for finding food.
Keywords: Animals; Olfactory Pathways; stravovací zvyklosti; sumci; čichové dráhy; Morphogenesis; morfogeneze; mikroskopie elektronová rastrovací; zvířata; Feeding Behavior; Microscopy, Electron, Scanning; Catfishes